Enhancing medical English proficiency: the current status and development potential of peer-assisted learning in medical education - Peixin Lin; Yuexin Cai; Sijia He; Xinxin Li; Yuanke Liang; Tian Huang; Juanyun Li; Baohang Lin; Gang Xin; Haoyu Lin (BMC Medical Education)
Abstract This narrative review investigates the current implementation and future potential of Peer-Assisted Learning (PAL) in medical education, specifically emphasizing its role in enhancing medical English proficiency. The article analyzes the effectiveness of PAL across various medical education contexts, including primary medical courses, doctor-patient communication, and standardized residency training. The findings indicate that PAL positively impacts student learning outcomes and promotes professional development, highlighting the necessity of its application in medical English instruction. However, implementing PAL faces several obstacles, such as limitations in student cognition and a singular interaction model. This review presents several application prospects, including scenario simulation and the integration of PAL with pedagogical methods such as Problem-Based Learning (PBL), Case-Based Learning (CBL), and Team-Based Learning (TBL). Ultimately, this review underscores the importance of PAL in medical English teaching and recommends future research directions to develop effective teaching models that optimize its implementation.